Pengaruh Kualifikasi Akademik Guru PAUD terhadap Pembelajaran Kurikulum Merdeka - Syifa Nisviati; Risbon Sianturi (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to analyze the effect of PAUD teachers' academic qualifications on independent curriculum learning. Teachers are scholars who will be obeyed and imitated by students. So that a teacher must have qualifications as physical evidence of quality obtained through education and the teaching profession. This research method uses qualitative research with a descriptive approach. Data collection techniques conducted by researchers through field observations, interviews, and documentation. The subjects of this research consisted of the principal and 5 teachers. The object of research includes the academic qualifications of PAUD teachers towards learning the Merdeka curriculum. Analysis of data collection is carried out through drawing conclusions from the findings studied. This research is located at Amal Sholeh Islamic Kindergarten in Tasikmalaya city. The results of this study indicate that there are differences in performance quality between qualified and linear teachers and unqualified and non-linear teachers. This certainly affects the effectiveness of learning, especially in the Merdeka Curriculum which requires teachers to be creative and innovative.